Moisture movement within concrete exposed to simulated hot arid/semi-arid conditions. Issue 6 (13th December 2020) - Alaswad, Gasim; McCarter, William John; Suryanto, Benny
Abstract : The ambient environment has a considerable influence on the permeation properties of the near-surface zone of exposed concrete (i.e. the cover zone). Monitoring the mass transport and flow processes and properties within this region is crucial in evaluating the long-term performance of concrete for a particular exposure condition. This paper presents an experimental study on both the spatial and temporal moisture movement within the surface region of concrete with and without supplementary cementitious materials. Prior to exposure, the samples were conditioned under two regimes representing poor and good curing; the samples were then exposed to a simulated hot environment with a diurnal temperature fluctuation of ∼20–40°C and ∼60% ambient relative humidity. Moisture movement within the surface region was monitored using discretised electrical conductivity measurements which, together with gravimetric measurements, allowed evaluation of the volumetric uptake and sorptivity of the concrete and the rate and depth of water penetration into the concrete cover zone; it is shown that when these are combined, the degree of saturation, effective porosity and total porosity of the surface region could be estimated. By evaluating the conductivity prior to and after water absorption, the zone of influence of wetting/drying action (i.e. the convective zone) could be evaluated.